Enhanced acoustic black hole energy harvesters with multipiezoelectric array designs. (1st April 2023) - Xiong, Defeng; Liang, Jingfu; Qiao, Yupei; Qi, Shuibao
Abstract: This study theoretically and numerically proposes vibroacoustic energy harvesting concepts based on acoustic black holes (ABHs) and piezoelectric materials. Various ABH configurations in planar structures have been explored and investigated from the perspective of flexural wave localization and energy confinement. Different piezoelectric energy transducers, attached to the center region of ABHs with loading circuits are designed. Energy harvester with arrayed two ABHs shows higher energy production density than a harvester with single ABH under the same driving conditions. The energy harvester with the combination of the arrayed ABHs and the multipiezoelectric arrays shows high output electrical power density and broadband features.